Fangchinoline as a kinase inhibitor targets FAK and suppresses FAK-mediated signaling pathway in A549. (April 2015) - Guo, Bingyu; Su, Jingyuan; Zhang, Tingting; Wang, Kaiwen; Li, Xiaoming
Abstract Background: Fangchinoline as a novel anti-tumor agent has been paid attention in several types of cancers cells except lung cancer. Here we have investigated the effect of fangchinoline on A549 cells and its underlying mechanism. Purpose: The purpose of this work was to study the effect of fangchinoline on A549 cells. Methods: Four lung cancer cell lines (A549, NCI-H292, NCI-H446, and NCI-H460) were exposed to varying concentrations (10–40 μmol/l) of fangchinoline to observe the effect of fangchinoline on the four lung cancer cell lines and to observe the changes of the lung cancer cell on proliferation, apoptosis, and invasion. Results: Fangchinoline effectively suppressed proliferation and invasion of A549 cell line but not NCI-H292, NCI-H446, and NCI-H460 cell lines by inhibiting the phosphorylation of FAK (Tyr397) and its downstream pathways, due to the significant differences of Fak expression between A549 and the other three cell lines. And all FAK-paxillin/MMP2/MMP9 pathway, FAK-Akt pathway, and FAK-MEK-ERK1/2 pathway could be inhibited by fangchinoline. Discussion: Fangchinoline effectively suppressed proliferation and invasion of A549 cell line by inhibiting the phosphorylation of FAK (Tyr397) and its downstream pathways. Conclusion: Fangchinoline could inhibit the phosphorylation of FAKp-Tyr397, at least partially. Fangchinoline as a kinase inhibitor targets FAK and suppresses FAK-mediated signaling pathway and inhibits the growth and the invasion in tumor cells which highly expressed FAK such as A549 cell line.